Early twentieth century atomic models: from classical physics to the introduction of quantum theory - Lopes, Cesar Valmor Machado (Circumscribere International Journal for the History of Science, 2009)
The present research examines the history of atomic models in the early twentieth century approaching the contributions of Joseph John Thomson, Hantaro Nagaoka, Ernest Rutherford, John William Nicholson and Niels Bohr and his contemporaries.